Association of non-high-density lipoprotein to high-density lipoprotein ratio (NHHR) with prognosis in cancer survivors: a population-based study in the United States - Xie, Wenxia; Liu, Huizhuo; Lin, Qiaoxin; Lian, Liyou; Liang, Bin (Frontiers in Nutrition, 2024)
Background: Patients with cancer frequently exhibit alterations in serum lipid profiles associated with chemotherapy. It has been reported that lipid distribution in mortality (overall association test P-value=0.48, nonlinear association test P-value=0.66). Considering the competitive risk of heart disease and cancer-specific mortality, there is no difference between the high and low NHHR groups, while the low NHHR group showed an increased risk of non-specific causes of death (p<0.001).The results of this study suggest that NHHR is an important indicator that is strongly associated with all-cause mortality in cancer survivors, and that this relationship may be influenced by the interaction of diabetes and smoking status. This finding may provide important information for future research and patient management.